2019
DOI: 10.1108/jec-10-2019-0103
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial social identity and stakeholders: the socio-economic implications

Abstract: Purpose Entrepreneurial identity involves identifying and exploiting opportunities to create value and wealth. Entrepreneurship contributes mainly to a firm’s efforts be exploited in a marketplace. The purpose of this paper is to analyse the relationship between the entrepreneurial social identities identified by Fauchart and Gruber (2011) and three primary stakeholders: investors, customers and employees. Design/methodology/approach Data were collected through online questionnaires from entrepreneurs who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Because of its scope, including work-life interaction and educating children [3], women's entrepreneurship has become a crucial aspect of the socio-economic transformation process [4], particularly in developing countries like Pakistan [5]. Women's entrepreneurship is viewed as a vehicle for converting available resources into valuable goods and services while creating employment opportunities that will ultimately lead to wealth creation [6,7] and social empowerment. In addition to their economic activities, women entrepreneurs also serve as role models that inspire other women to pursue entrepreneurship [8].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its scope, including work-life interaction and educating children [3], women's entrepreneurship has become a crucial aspect of the socio-economic transformation process [4], particularly in developing countries like Pakistan [5]. Women's entrepreneurship is viewed as a vehicle for converting available resources into valuable goods and services while creating employment opportunities that will ultimately lead to wealth creation [6,7] and social empowerment. In addition to their economic activities, women entrepreneurs also serve as role models that inspire other women to pursue entrepreneurship [8].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars from different perspectives have studied the field of entrepreneurship. Entrepreneurial intentions and activities are considered as an opportunity to create worth and value in the economy (Estrada-Cruz et al, 2019). The growth of any venture depends upon the personal, social and managerial capabilities of the entrepreneur (Agarwal and Lenka, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, Kochan et al (2003) showed that the intense involvement of women in the boardroom may increase the cost of decisionmaking because of the possibility of conflicts in the executive team, hindering firm performance. Du Rietz and Henrekson (2000), and Estrada-Cruz et al (2019) indicated that firms with a greater appearance of women in boardrooms probably fail to meet firm expectations, such as lower profits and growth in sales.…”
Section: Board Diversitymentioning
confidence: 99%